(untitled) (The Review of Diabetic Studies, 2025)
The geographical limits of Saudi Arabia are a serious impediment to the quick delivery of emergency services to patients with acute illness, but a structured, quantitative evaluation of how its service of air ambulance service changes the survival of patients could not be located. Hence, the current research was conducted to determine whether air ambulance transportation is associated with a survival benefit for critical cases compared to ground transportation, in terms of injury severity. The retrospective cohort study was conducted, relying on the data of 600 patients (300 in each cohort) transported in the period between 2020 and 2023. The multivariate logistic regression was used to assess the in-hospital mortality, which is adjusted by the Injury Severity Score (ISS), Glasgow Coma Scale (GCS), and age. The unadjusted mortality rate was more frequent in the air cohort (30.0 0 1 vs. 15.0 0 1, 0 = 2027, p 0 001), as they were more acute. After adjustment, however, there was an independent negative relationship between air transport and a 48 per cent decrease in the odds of dying (Adjusted Odds Ratio = -0.52, 95 per cent CI = -0.31-0.85, p = 0.009). Kaplan-Meier analysis also supported a significantly higher 30-day survival rate of the air cohort (72.1%, 58.5%, log-rank p = < 0.001). This research provides solid information that emergency flights in Saudi Arabia are highly effective in saving the lives of severely ill and injured individuals and can, therefore, be an important part of the national emergency care infrastructure. The results highlight the importance of en-route care to mitigate the threat of long transportation periods in geographically dispersed areas.